Cross-cultural Corporate Identity Curriculum Model: A Needs Analysis - Nik Narimah Nik Abdullah; NURFARADILLA MOHAMAD NASRI; Muhammad Helmi Norman; Juritah Misman (International Journal of Evaluation and Research in Education (IJERE), 2022)
To give input on the developmental needs of a sustainable curriculum, needs analysis is one of the most essential stages of data collection in order to provide information for systematic analysis. The main objective of this study is to investigate a needs analysis for the Graphic Design Program in higher learning institutions based on a cross-cultural corporate identity curriculum model. Generally, the study involved a semi-structured interview conducted on twelve participants which comprised of ten lecturers from the Graphic Design Program working in local higher learning institutions and another two experienced graphic designers working in the public sector. Qualitative analysis of data was gathered from the semi-structured interviews and later transcribed and analyzed thematically. Three main themes were recorded: (i) design based on local cultural identity, (ii) cross-cultural curriculum and (iii) student-centered teaching and learning. Data findings concluded that the majority of the study participants were inclined towards a cross-cultural corporate identity curriculum model for the Graphic Design Program. Results showed that study participants agreed that cross-cultural needs in the field of graphic education. It could provide a platform for exploration in teaching and learning in creating local-style designs which are unique and creative.